Review of modern techniques and analysis of patient outcomes with benign familial pemphigus Gougereau–Haley–Haley - Marianna B. Drozhdina; Sergey V. Koshkin (Vestnik Dermatologii i Venerologii, 2024)
Benign familial pemphigus (BFP) Gougereau–Haley–Haley is a rare autosomal dominant genodermatosis caused by mutations of the ATP2C1 gene responsible for the function of calcium-dependent ATPases regulating calcium sequestration in the Golgi apparatus. The article provides an overview of modern methods of treatment of various groups of drugs, including drugs for topical treatment (topical glucocorticosteroids, calcipotriol, combined drugs), systemic drugs (glucocorticosteroids, apremilast), injection techniques (intradermal administration of botulinum toxin) currently used.